Body Image and Sociocultural Predictors of Body Image Dissatisfaction in Croatian and Chinese Women - Stojcic, Ivana; Dong, Xiawei; Ren, Xiaopeng (Frontiers in Psychology, 2020)
In the current paper, two different studies were designed to investigate body image dissatisfaction and perception of the attractive female body in Chinese and Croatian women and men using the correlational and experimental study research design. Study 1 comprised 266 Chinese (160 women; 106 men) and 261 Croatian participants (161 women; 100 men). Women from both countries were asked to complete the measures of the Contour Rating Scale, SATAQ – 4, Body Area Scale and demographic data, while men were asked to complete the measures of the Contour Rating Scale and demographic data via online surveys. The obtained results indicated that thin internalization predicted body image dissatisfaction in both samples. Besides, while both samples scored relatively high on thin-ideal internalization, Chinese women, who were also in general less satisfied with their body image, had higher scores. Chinese women also scored higher on musculature internalization and felt more pressure from family, friends, and media to conform to standard beauty norms compared to Croatian women. The samples also differed in their perceptions of preferable body size, where Chinese women had a more negative perception of their actual body size. The obtained results furthermore revealed that Chinese men preferred thinner women compared to Croatian men. Moreover, both samples misjudged what their female counterparts found attractive, thinking that women wanted to have even thinner bodies than they actually reported. Similarly, women from both cultures revealed a preference for thinner figures than the ones selected as the most attractive by the opposite sex. Finally, in Study 2, experimental manipulation of thin-ideal was used to examine whether thin priming affected body image dissatisfaction. The obtained results revealed that when primed with thin-ideal women from both countries felt lower satisfaction with their body size. The observed effect was stronger for Chinese participants. Limitations of the current study are discussed in the conclusion.